Management of The Main Course Learning Management System (LMS) By Lecturers In Promoting A Quality Class: : A Study In English Literature Study Program, STBA Sebelas April Sumedang - Denny Kodrat (UICELL, 2020)
Distance learning or education is a hot issue discussed by educators (McVay and Rockers, 2007). The use of Information and Communication Technology (ICT) is introduced by the government and other stakeholders. The study investigates how the lecturers use the Learning Management System (LMS) in conducting a quality class. The study used a qualitative approach with a descriptive method. This approach is aimed at uncovering phenomena experienced by lecturers (Moleong, 2005). The researcher becomes a key instrument who cannot be delegated (Creswell, 1998; Sugiyono, 2005). The finding then is sufficiently reconstructed by keeping a natural setting, so the finding data can be depicted as the aims of the research are expected. The study was conducted at the English Literature Study Program, STBA Sebelas April Sumedang. In-depth interviews were performed with 5 (five) lecturers who are in charge of the main subject/course in the study program. The result is the use of LMS needs lecturers' creativity and a new mindset, then the course objective can be obtained and the student’s center paradigm is maintained. Pembelajaran atau Pendidikan Jarak Jauh (PJJ) menjadi perhatian utama para pendidik (McVay dan Rockers, 2007). Penggunaan teknologi informasi dan komunikasi (TIK) diperkenalkan oleh pemerintah dan pemangku kepentingan. Penelitian ini mengkaji bagaimana dosen menggunakan Learning Management System (LMS) dalam melaksanakan perkuliahan yang bermutu. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Pendekatan ini ditujukan untuk membuka fenomena yang dialami oleh dosen (Moleong, 2005). Peneliti menjadi instrumen kunci yang tidak dapat diwakilkan (Creswell, 1998; Sugiyono, 2005). Temuan penelitian kemudian direkonstruksi dengan cara mempertahankan situasi natural. Data temuan kemudian digambarkan sesuai dengan tujuan penelitian yang diharapkan. Penelitian ini dilakukan di Program Studi Sastra Inggris, STBA Sebelas April Sumedang. Wawancara mendalam dilakukan terhadap 5 (lima) dosen yang mengampu mata kuliah inti program studi. Hasil penelitian menunjukan bahwa penggunaan LMS mengharuskan kreativitas dan mindset baru para dosen, sehingga tujuan perkuliahan dapat tercapai dan paradigma belajar bertumpu pada mahasiswa dapat dilaksanakan.